Facile synthesis of novel blue light and large Stoke shift emitting tetradentate polyazines based on imidazo[1, 5-a]pyridine. (May 2016) - Volpi, G.; Garino, C.; Conterosito, E.; Barolo, C.; Gobetto, R.; Viscardi, G.
Abstract: A facile double condensation procedure, through both standard and microwave heating, provides a versatile one step approach for the synthesis of multidentate nitrogen heterocyclic ligands containing the imidazo[1, 5-a]pyridine moiety. The obtained compounds show interesting optical properties: blue fluorescent emissions, moderate quantum yields and large Stokes shifts, enabling their technological application. Graphical abstract: